Innovative Food Systems Solutions Portal and online interactive portal that hosts and connects groups around innovative food systems solutions for healthy diets and a healthy planet - CGIAR Research Program on Water, Land and Ecosystems (2020)
A Delphi study was completed to surface and explore innovations, and the structure of the portal was set up and improved based on several outreach and feedback sessions.